2020
DOI: 10.3906/sag-1909-183
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress parameters in patients with ascending aortic dilatation

Abstract: Background/aim: This study aimed to determine plasma thiol, disulphide, and serum ischemia-modified albumin (IMA) levels and ferroxidase activity in patients with ascending aorta dilatation (AAD) in comparison to those without AAD and to evaluate the predictive value of these oxidative stress parameters for AAD. Materials and methods: This study was designed as a cross-sectional study of 184 patients who applied to our cardiology clinic. Our study population consisted of patients with AAD (n = 85) and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Further analysis revealed the association of TTL with fatal MI risk. However, Erdoğan and colleagues (2020) highlighted a different finding in which higher levels of TTL were shown in the control group than in the ascending aortic dilatation (AAD) group [ 39 ]. Lower TTL appears to confer a higher risk for AAD development and independently predicts the diameter of ascending aortic.…”
Section: Oxidant Biomarkers In the Diagnosis And Prognosis Of Cvdmentioning
confidence: 99%
“…Further analysis revealed the association of TTL with fatal MI risk. However, Erdoğan and colleagues (2020) highlighted a different finding in which higher levels of TTL were shown in the control group than in the ascending aortic dilatation (AAD) group [ 39 ]. Lower TTL appears to confer a higher risk for AAD development and independently predicts the diameter of ascending aortic.…”
Section: Oxidant Biomarkers In the Diagnosis And Prognosis Of Cvdmentioning
confidence: 99%
“…In aortic dissection patients, it was previously found that aortic diameter is related with cardiac hypertrophy, and in the same study, marked correlation was found between aortic diameter and left ventricle mass index (LVMI) [ 15 ]. Similarly, Erdogan et al found a statistical relationship between LVMI and ascending aorta size, whereas on the other hand, they found significant difference between patients with dilated ascending aorta and normal populations, in regards to LVDd, LVPWd, LVEF, and LAD [ 16 ]. Similarly, a significant relationship was reported by Iarussi et al between aortic diameter and cardiac parameters, such as LVDd, LVDs and LVMI index, in an analysis of aortic dissection patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that oxidative stress plays a leading role in the development of aortic aneurysms (2)(3)(4). The remodeling of the aortic wall is substantially associated with an impaired balance between MMP and its inhibitors (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…As it is a clinically silent entity, one of the main reasons for mortality in adults is an ascending aortic aneurysm (AscAA) (1). Familial predisposition, hemodynamic force, aortic transmural inflammation, destructive remodeling, and oxidative stress in the extracellular matrix have contributed to the pathophysiology of AAD (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%